2020
DOI: 10.1002/admi.202001317
|View full text |Cite
|
Sign up to set email alerts
|

Electrowetting‐Controlled Dropwise Condensation with Patterned Electrodes: Physical Principles, Modeling, and Application Perspectives

Abstract: Patterning the wettability of solid surfaces is a successful strategy to control the dropwise condensation of vapor onto partially wetting solid surfaces. The condensation of water vapor onto electrowetting‐functionalized surfaces is studied with structured co‐planar electrodes. A detailed analysis of the experimental distribution of millions of drops reveals that despite the presence of contact angle hysteresis and the occurrence of random drop coalescence events, the preferential drop positions closely follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…[35] We will consider elliptical discs. Their electrical capacity has been shown to be proportional to 2𝜋a e ∕K(k) where a e is the length of the larger axis of the ellipse, K(k) is the complete elliptic integral of the first kind, and k ≡ √ 1 − (b e ∕a e ) 2 , where b e is the length of the smaller axis. Actually, in electrostatics the capacity is two times larger.…”
Section: Sources Of Elliptical Shapementioning
confidence: 99%
See 1 more Smart Citation
“…[35] We will consider elliptical discs. Their electrical capacity has been shown to be proportional to 2𝜋a e ∕K(k) where a e is the length of the larger axis of the ellipse, K(k) is the complete elliptic integral of the first kind, and k ≡ √ 1 − (b e ∕a e ) 2 , where b e is the length of the smaller axis. Actually, in electrostatics the capacity is two times larger.…”
Section: Sources Of Elliptical Shapementioning
confidence: 99%
“…In a number of cases, such processes occur in highly heterogeneous structures. Examples are as diverse as evaporation of multiple sessile drops, water-vapor condensation on structured surfaces, [1,2] dissolution of nano-bubbles or nano-droplets attached to surfaces, [3] plant transpiration via stomata, [4] currentinduced concentration polarization of arrays of microelectrodes, [5][6][7] solvent and solute flows in thin-film composite membranes, [8] soil drainage using perforated tubes, [9,10] or fluid flows in composite materials containing perforated layers. [11,12] A useful mathematical idealization of such structures is impervious domains alternating with zones of extremely high "conductivity" (or permeability or diffusivity depending on the process).…”
Section: Introductionmentioning
confidence: 99%
“…To further enhance drop shedding, recent investigations have revealed that surfaces that are biphilic (i.e., surfaces with both hydrophilic and hydrophobic patterns) increase water and fog collection rates. , The innovation of these surfaces was inspired by nature, , such as cacti, , Namib desert beetles, , and Moloch Horridus lizards, which have unique microstructured surfaces increasing favorable contact angle hysteresis on their skin to collect and transport water efficiently for ingestion. The fabrication of the bioinspired interfaces is of great importance to enhancing water harvesting efficiencies, and emerging advanced manufacturing techniques have shed light on biomimicry potential with varying degrees of success.…”
Section: Introductionmentioning
confidence: 99%